Pressure dependence of resistivity and magnetic properties in a Mn1.9Cr0.1Sb alloy - Sharma, Vinay (2018)
We report magnetic-field and hydrostatic pressure dependent electrical resistivity and magnetic properties of a Mn1.9Cr0.1Sb alloy. Upon cooling, the magnetization of Mn1.9Cr0.1Sb exhibits a first-order ferrimagnetic to antiferromagnetic transition at the exchange inversion temperature, TS = 261 K under a 0.1 T magnetic field. Our experimental results show that TS decreases with increasing magnetic field but increase with increasing hydrostatic pressure. The pressure induced transition is accompanied by a large positive baro-resistance of 30.5% for a hydrostatic pressure change of 0.69 GPa. These results show that the lattice parameters as well as the bond distance between Mn-Mn atoms play a crucial role in the magnetic and electronic transport properties of Mn1.9Cr0.1Sb. This sample also exhibits a large inverse magnetocaloric effect with a magnetic entropy change of ΔSm = +6.75 J/kg.K and negative magnetoresistance (44.5%) for a field change of 5 T at TS in ambient pressure which may be useful for magnetic cooling and spintronics applications.